Analysis of the Management and Recording of Petty Cash at PT Barelang Elektrindo Era Cemerlang in Batam City: Analisis Pengelolaan dan Pencatatan Kas Kecil pada PT Barelang Elektrindo Era Cemerlang di Kota Batam - Sara Desenberia Aritonang; Viola Syukrina E Janrosi (Perkumpulan Doktor Indonesia Maju, 2020)
PT Barelang Elektrindo Eracemerlang comes from sales services in the form of services. In operational activities, because it is not a manufacturing company, it does not have fixed expenses, but there are many expenses in nominal amounts that are not large, so that the role of petty cash is very influential in carrying out the activities of a company that is engaged in other events. In addition, the management of the company's financial transactions and operations is still done manually, resulting in various problems in the absence of a computerized system. In this study the authors used two X variables consisting of management (X1), recording (X2) and one Y variable, namely petty cash. The population in this study is the financial statements of PT Barelang Elektrindo Eracemerlang from 2014 to 2018. The sample in this study is financial reports for one year, January to December 2018. The result of research are Petty cash management at PT Barelang Elektrindo Era Cemerlang uses changing the fund system, where there are several established procedures for carrying out operational activities, such as the formation of petty cash funds, expenses, and refilling of petty cash funds. The petty cash management and recording system at PT Barelang Elektrindo Era Cemerlang has not been in accordance with existing accounting principles, seen from cash management that uses 2 (two) methods directly so that petty cash disbursements cannot be controlled or controlled properly.